Kyrgyz Republic : Country Procurement Status Review - World Bank (Washington, DC, 2013)
The Country Procurement Status Review (CPSR) report was prepared on the basis of the findings from a joint World Bank (WB)/Asian Development Bank (ADB) mission that visited the Kyrgyz Republic in February 2012. The main objectives of the CPSR are: (a) to analyze the Kyrgyz public procurement system, including the existing legal framework, organizational responsibilities, control and oversight mechanisms, capacity, and current procedures and practices, as well as how well these work in practice; and (b) based on these analyses and review, to identify key areas for improvement in public procurement and prepare an action plan for implementation of related revisions to the public procurement system. The report has three chapters: (I) Introduction; (II) Assessment of the Public Procurement System; and (III) Recommendations and Action Plan. A summary of the main findings and recommendations is provided in the Executive Summary at the beginning of the report. The detailed assessment of the Baseline Indicators is provided in Annex C. Additional Provisions for National Competitive Bidding under WB-financed operations is provided in Annex D.